Inclusion of users with Intellectual Disabilities and Autist Spectrum Disorder in university libraries - Wellichan, Danielle da Silva Pinheiro; Fonseca , Kátia de Abreu (InCID: Revista de Ciência da Informação e Documentação, 2023)
To comply with the principles of inclusion, university libraries must be prepared to embrace users with disabilities and other conditions included in the Target Public of Special Education (PAEE). However, the lack of knowledge regrading needs, skills and potential, reinforces the gap in the relationship between professionals and users, especially for those with Intellectual Disability (ID) or autism spectrum disorder (ASD). Due to invisibility and the different specificities needed in each case, library service, use and frequency can be harmed if certain aspects are disregarded. Thus, which initiatives are implemented by libraries to serve these users and ensure they use and frequent the library? To answer these questions, bibliographic research was conducted in Portuguese, Spanish and English in national and international databases, starting from the 2019 Census, to identify what different university libraries offer to such users. Results show possible partnership initiatives with the users themselves, demanding changes in human relationships which can significantly contribute to creating more harmonious and inclusive environments for all.